Kompetensi Kepribadian Guru dalam Membentuk Karakter Peserta Didik - Abu A’la Al Maududi; Nur Fadillah Dalimunthe; Malikul Sholeh As Salim; Khairun Nisa (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This study explores the profound impact of teacher personality competence on student character formation through a descriptive narrative lens grounded in the sociology of education. Education is not merely a technical transfer of knowledge but a complex social process where the teacher acts as a pivotal moral agent and role model. By synthesizing classical sociological paradigms—Functionalism, Conflict Theory, and Symbolic Interactionism—with contemporary empirical evidence, this article argues that a teacher's personality is a dynamic social construct that shapes the "hidden curriculum" and the overall school climate. The narrative analysis reveals that traits such as empathy, integrity, and social justice are not just individual attributes but essential tools for moral socialization and the internalization of collective values. The study finds that teachers who embody these virtues foster a sense of social belonging and ethical responsibility in students, effectively bridging the gap between individual identity and societal expectations. The article concludes that strengthening teacher personality competence is a strategic imperative for developing a resilient and morally grounded generation, recommending integrated professional development that emphasizes the teacher's role as a moral authority in the 21st-century social landscape.